"Borrowing Happiness from the Future": Exploring College Students' Own Experiences on Health-Related Lifestyles. Issue 2 (3rd April 2017) - Chen, Hsin-Yu; Yarnal, Careen; Bram, Barry
Abstract: Combining the theory of emerging adulthood with self-authorship, the authors utilized students' reflection papers ( n  = 111) to explore their current lifestyles and reasons behind behavioral changes. Decreased physical activity, increased substance use, irregular sleep patterns, and unhealthy dietary habits emerged after students transitioned to college. These shifts reflect the complex interplay among changes in living environment and interpersonal relationships, time and finance allocation, and interrelated behaviors. The study demonstrates that integrating a three-phase time diary project with cognitive learning elements prompts self-awareness about students' own lifestyles and motivates them to become healthier. These findings may help college administrators refine health promotion programs and demonstrate the time diary's value in offering students an opportunity to examine their lifestyles.